Intercorporate loans and tunneling under uncertainty: Empirical evidence from Indonesia - Purwanto, Purwanto (Asian Management and Business Review, 2026)
Intercorporate loans are often used in business groups, especially those with pyramidal ownership structure, which is a characteristic common among Indonesian companies. Intercorporate loans in business groups can be beneficial but also presents a number of risks on agency issues, such as in acquisition of rights of minority shareholders by tunneling. This study aimed to identify the factors influencing tunneling through intercorporate loans in public companies in Indonesia. The study was conducted on companies listed on the Indonesia Stock Exchange, excluding banks and financial institutions. A period of uncertainty was observed during the global financial crisis period of 2008. The data were analysed using logistic regression analysis. The results are as follows: A pyramidal ownership structure, family ultimate controller, and foreign ultimate controller had positive influence on intercorporate loans tunneling.